Nurturing Students’ Spirituality through Holistic Instructional Communication Implementation: a Case Study from Indonesian Islamic Higher Education - Fa'atin, Salmah; Syukur, Fatah; Rohman, Abdul; Primarni, Amie (Program Studi Pendidikan Agama Islam, 2025)
Spiritual strengthening of Islamic Higher Education students through learning activities is not only enough rely on teaching materials, but also need a new instructional communication model. This study aims to investigate the implementation of Holistic Instructional Communication (HIC) for nurturing students’ spirituality of the Sufism and Psychotherapy Study Program. This paper reports a qualitative and quantitative study about the implementation of HIC for students of Indonesian Islamic higher education in Kudus and Semarang, Indonesia. This study was derived from interviews with Islamic education lecturers about instructional communication patterns at the universities. It also included observations of instructional communication implementation in the classroom. Data were garnered through a qualitative and quantitative approach to enable substantial descriptive data collection about how students’ spirituality can be nurtured by implementation of holistic instructional communication. The results showed that the holistic instructional communication (HIC) model that had been implemented was a message-oriented circular communication model, so that spiritual strengthening was not optimal. Therefore, HIC model was implemented based on the holistic education paradigm by adapting Barnlund's transactional communication model which is oriented towards the construction and negotiation of meaning for student spiritual strengthening. The HIC model has met the valid criteria, is considered practical and effective for strengthening student spirituality based on the validation result 89.02% and 85.75% of students’ activities. The conclusion of the effectiveness of the model is based on the increase in the spiritual dimension of students after participating in learning with the HIC model, with an average percentage gain score is 59% and an average normalized gain score (N-gain) is 0.6 with a fairly effective category. This confirms that efforts to strengthen student spirituality can be done by implementing the HIC model.